Budidaya Sayuran Sistem Hidroponik bagi Kelompok Guru dan Siswa Pesantren Al-Quran Yayasan Babussalam Selayar - Abd. Muis; Ismail Ismail; Muhiddin Palennari (Universitas Negeri Makassar, 2018)
Conventional vegetable cultivation using land planting media in the area of the Al-Quran IslamicBoarding School is very difficult to do due to time constraints and technical abilities. This condition is experiencedby the academics of the Babussalam Al-Quran Islamic Boarding School in Selayar Regency. The school is locatedin an area of about 7000 m2 and it is possible to cultivate vegetables in a hydroponic system. The program aims toincrease: 1) the knowledge and technical skills of vegetable cultivation in hydroponic systems for academics of theAl-Quran Islamic Boarding School, 2) the skills of partner citizens about making nutrient solutions usinghydroponic systems which are easy and cheap, 3) improve food (vegetable) resilience for partner citizens. Themethods used were training, demonstration, and assistance with a Participatory Rural Appraisal (PRA) approach.Activities carried out include training and demonstrations on techniques for cultivating vegetables in hydroponicsystems, making the hydroponic solutions that are easy and inexpensive, and mentoring program of the vegetablecultivation by using hydroponic systems. The specific target achieved was an increase in partner knowledge andskills about vegetable cultivation techniques using hydroponic systems for academics of Al-Quran Islamic BoardingSchool as well as an increase of partner skills about making cheap and easy hydroponic system solutions and food(vegetable) security for partner citizens.